The Accessory Nature of the Penalty and the Peculiarities of Payment - Nandoshvili, Ekaterine (European Scientific Journal, ESJ, 2021)
This paper focuses on analyzing the accessory nature of the penalty, the peculiarities of its payment, and the legislative provisions regulating the penalty. It also presents their shortcomings and criticizes the wrong opinions in the legal literature on the concept and types of the penalty. The penalty is considered as the institutions with only accessory nature. Reduction of the penalty requires the debtor’s counterclaim, without which the court is deprived of the possibility of reducing the penalty. The provision of Article 417 of the Civil Code is considered a serious legislative gap by the paper. The novelty is the provisions of the paper and the necessity of introducing norms on legal penalties in the Civil Code is substantiated, without which the case law may become a factor of unjustified violation of the rights of the participants of the private relations. There is also substantiated provision, which refutes the validity of the opinion of the authors who exclude the initiative of the court in the issue of reduction of the penalty. The aim of this paper is to analyze certain aspects of the regulation of penalties, which, together with the theoretical aspects, have practical significance that will provide better understanding of a number of issues as well as the correct qualification of the rights and obligations arising from the payment of penalties. Logical and systematic analysis of norms, as well as comparative-legal methods, are used to achieve the above-mentioned goal. Using these methods, it is possible to determine the progressiveness of Georgian law norms and to identify existing gaps in them. This further provides a better understanding of their content so as to develop suggestions and recommendations to improve the norms and practices. Problems are analyzed on the examples of Georgian and German civil law. In terms of types and concepts of penalties, common characteristics and shortcomings between Georgian and German models were revealed. The efficiency of the Georgian model was also examined in terms of establishing the penalties. The study revealed that the Civil Code of Georgia determines the type of contractual penalty and allows its reduction. Based on this, a wrong conclusion has been made in science and practice about the existence of only one type of penalty in Georgian law. The circumstance that private law legislation does not consist solely of the Civil Code was not taken into account. The paper examines the applicable legislation of Georgia, which sometimes does not even use the term “penalty”, but actually provides for a legal penalty in various provisions. It is inevitably necessary to reflect the norms in detail in order to regulate the payment of legal penalties in the Civil Code of Georgia.